Penerapan Jaringan Bisnis Legenda Kopi Pada Marketplace Aplikasi Facebook Sebagai Platform Jaringan Bisnis - Vega Permana; Resya Dwi Marselina (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2024)
Social media platforms have now developed over time, now social media is not only used as a way of communicating and sharing information, now social media provides a place for business people to develop their business and promote their products easily at no cost. By utilizing the Facebook marketplace, a company will have a strong business network. This article discusses the application of the coffee legend business network on the Facebook application marketplace as a networking platform in the digital era. The method used in this article is a qualitative method which is done by collecting information through various literature in several journals related to the title of this article. The results of the analysis through literature are building broad business applications in the digital era using the Facebook marketplace platform.